Exploring Socio-Religious Dynamics in Sujiwo Tejo's Republik #Jancukers and Tuhan Maha Asyik: A Gadamerian Hermeneutic Analysis - Bintari, Intan Permata Dewi Surya (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study investigates Sujiwo Tejo's literary works Republik #Jancukers and Tuhan Maha Asyik through the lens of social-religious commentary, utilizing Gadamer's hermeneutics as the analytical framework. These works are examined for their implicit messages regarding socio-religious concepts, reflecting the author's broader intention to contribute to sociological understanding through literature. Employing a qualitative research methodology with a hermeneutic approach, this library-based research focuses on the integration of social and religious thought within the texts. The analysis applies Gadamer's concepts of historical context and fusion of horizons to explore the depiction of religious social interactions, categorizing them into vertical (individual or group interactions with the divine) and horizontal (interactions among believers). The findings reveal that Tejo's works intricately weave socio-religious themes into their narrative fabric, offering a nuanced exploration of religious interactions. Through Republik #Jancukers and Tuhan Maha Asyik, Tejo presents a multifaceted view of vertical interactions, where individual and collective engagements with the divine are depicted as dynamic and often critical. In contrast, horizontal interactions are portrayed as reflective of the complexities and tensions within religious communities.